PENGEMBANGAN BUKU AJAR DIGITAL KALKULUS I DENGAN SOFTWARE SIGIL UNTUK MENINGKATKAN MOTIVASI BELAJAR IMPLEMENTASI KAMPUS BERDAMPAK - Taqwa, Muhammad (Universitas Pancasakti, 2025)
This research aims to create a valid, practical, and effective digital textbook that positively impacts student learning motivation. The development research is based on the 4 D model of Thiagarajan: (1) definition, (2) design, (3) development, and (4) dissemination. The research subjects involve students from the Mathematics Education Study Program at STKIP Andi Matappa and Khairun University. The research instruments consist of a textbook validation sheet, a practicality sheet, and a learning motivation test. The results conclude that the digital textbook has high validity, the practicality sheet has a practical score, and student learning motivation has increased, with an average score at the medium level. With the application of the digital calculus I textbook along with the valid, practical, and effective Sigil software, student learning motivation has increased